2013
DOI: 10.1371/journal.pone.0070532
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for the Circulation of Equine Encephalosis Virus in Israel since 2001

Abstract: Equine encephalosis virus (EEV) distribution was thought to be limited to southern Africa until 2008 when we reported EEV in Israel. It was then assumed that the clinical presentation resembled the initial incursion in Israel. To investigate further we conducted a retrospective analysis of equine sera, which had been collected for diagnosis of other suspected diseases, via serum neutralisation test. The data demonstrated that EEV was circulating as early as 2001 with incidence ranging from 20–100% for time per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…EEV in an important arbovirus that has been reported to be endemic in Israel since 2001 (Wescott et al 2013). EEV is transmitted through the bites of certain Culicoides spp., and has relatively mild clinical manifestations in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EEV in an important arbovirus that has been reported to be endemic in Israel since 2001 (Wescott et al 2013). EEV is transmitted through the bites of certain Culicoides spp., and has relatively mild clinical manifestations in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Since then it was reported in several locations in East and West Africa, as well as in Israel (Mildenberg et al 2009;Oura et al 2012;Attoui & Jaafar 2015). Retrospective studies from Israel demonstrated that this virus was present in the horse population from at least 2001 (Wescott et al 2013), and that the prevalent strain in Israel was more similar to a strain isolated in Gambia than to the South African strains (Howell et al 2002;Aharonson-Raz et al 2011;Oura et al 2012). It was also demonstrated that EEV seroprevalence and rate of infection varied at different time points, and was influenced mainly by herd immunity and weather conditions (Aharonson-Raz et al 2015).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For some affected horses, lack of appetite and some degree of edema have been reported as secondary complications ( 2 ). Equine encephalosis virus (EEV; family Reoviridae , genus Orbivirus ) was first isolated from horses in South Africa in 1967 and was considered endemic to southern Africa until an outbreak was reported in Israel in 2008 ( 3 ). Reports of EEV circulation in Israel indicated that the virus is not limited to a particular region and raised concerns about the risk for its spread to other countries where competent hosts and vectors are present ( 3 ).…”
mentioning
confidence: 99%
“…Equine encephalosis virus (EEV; family Reoviridae , genus Orbivirus ) was first isolated from horses in South Africa in 1967 and was considered endemic to southern Africa until an outbreak was reported in Israel in 2008 ( 3 ). Reports of EEV circulation in Israel indicated that the virus is not limited to a particular region and raised concerns about the risk for its spread to other countries where competent hosts and vectors are present ( 3 ). A recent study examining EEV seroprevalence in Israel, Palestine, and Jordan has emphasized the potential risk for invasion of pathogens into new ecologic niches ( 4 ).…”
mentioning
confidence: 99%